Geochemistry of Ophiolite Complex in North Konawe, Southeast Sulawesi - Ronaldo Irzon; Baharuddin Abdullah (Pusat Teknologi Bahan Galian Nuklir - BATAN, 2016)
ABSTRACTSoutheast Sulawesi is crosscutted by Lasolo Fault into two geological provinces: Tinondo and Hialu. Tinondo Geological Province is occupied largely by Ophiolite Complex in the northern part of Southeast Arm of Sulawesi. No study was conducted in relation to the geochemistry composition of Ophiolite Complex in North Konawe Regency. The aim of this study is to describe the ultramafic rock of the Ophiolite Complex in North Konawe Regency using field, geochemical, and petrographical analysis. Megascopically, the selected nine samples are described as greyish to blackish and fine to medium grains ultramafic rocks, which consist of pyroxene and olivine. Microscope, X-Ray Fluorescence (XRF), and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) devices were used to obtain both petrography and geochemistry data. Major oxides data confirm that the selected samples are classified into ultramafic rocks as SiO2, MgO, and Fe2O3T are the most abundant oxides. The studied samples presumably came from arc tholeiitic environment tectonic setting. Ultramafic rocks often contain promising economic metals whereas the average numbers of Ni, Mn, Cr, and Co of this study are 2,675; 1,074; 2,386; and 117 ppm respectively. The rocks are generally enriched in high field strength elements whilst rare earth elements value are low, ranging from 2.11 to 7.10 ppm. Microscopically, samples can be classified into three groups: olivine-hornblende pyroxenite, lherzolite, and olivine websterite. Geochemical data describes more about the discriminant analysis of the groups. ABSTRAKWilayah Sulawesi Tenggara dipotong oleh Sesar Lasolo yang membagi daerah ini menjadi dua lajur: Tinondo dan Hialu. Lajur Tinondo diisi sebagian besar oleh Komplek Ophiolit, yang berada di bagian utara dari Lengan Tenggara Sulawesi. Belum ada studi yang terfokus kepada kandungan geokimia Komplek Ophiolit tersebut di wilayah Kabupaten Konawe Utara.Studi ini bertujuan untuk mempelajari karakter batuan ultramafik dari Komplek Ophiolit di Kabupaten Konawe Utara melalui kegiatan lapangan, analisis geokimia, dan analisis petrografi. Secara megaskopis, sembilan contoh batuan terpilih teridentifikasi sebagai batuan ultramafik berwarna kelabu hingga hitam, berukuran butir sedang hingga halus, dan mengandung piroksen maupun olivine. Perangkat mikroskop, X-Ray Fluorescence (XRF), dan Inductively Coupled Plasma Mass Spectrometry (ICP-MS) dimanfaatkan untuk memperoleh data geokimia maupun mikroskopis. Data oksida utama mengklasifikasikan contoh terpilih ke dalam batuan utramafik dengan SiO2, MgO, dan Fe2O3T sebagai oksida dengan kelimpahan tertinggi. Contoh terpilih mungkin terbentuk pada lingkungan busur tektonik tholeitik. Batuan ultramafik sering mengandung logam ekonomis dengan kadar rata-rata Ni, Mn, Cr, dan Co pada studi ini adalah: 2.675, 1.074, 2.386, dan 117 ppm secara berurutan. Batuan telah mengalami pengayaan unsur high field strength elements meskipun dengan kadar unsur tanah jarang yang rendah, berkisar dari 2,11 hingga 7,10 ppm. Secara petrografi, batuan terpilih dapat dibagi menjadi tiga kelompok: olivine-hornblende pyroxenite, lherzolite, and olivine websterite. Data geokimia menjelaskan lebih lanjut mengenai perbedaan dari kelompok-kelompok tersebut.